THE IMPACT OF OVERSEAS CSR IMPLEMENTATION ON LIFTING PERFORMANCE AND CORPORATE PROFITABILITY AT PERTAMINA INTERNATIONAL EP: A SEM-PLS APPROACH - Nurul Intan Permanasari; Andi Mardhotilla; Jerry Heikal (RADJA PUBLIKA, 2025)
This study investigates the effect of overseas Corporate Social Responsibility (CSR) on two performance outcomes of Pertamina International EP (PIEP): lifting (Y1) and corporate profit (Y2). Using a quantitative, explanatory design, we compiled 32 observations from four operating areas (Malaysia, Iraq, Algeria, HQ-International) across 2018–2025. CSR is modeled as a latent construct (X) with three reflective indicators CSR_Education, CSR_Environment, and CSR_Overseas while Y1 is measured by lifting_bpd and lifting efficiency, and Y2 by revenue and net profit. Data were analyzed with SEM-PLS (SmartPLS 4). The measurement model meets all thresholds (outer loadings ≥0.70; AVE ≥0.50; CR and Cronbach’s alpha ≥0.70), with particularly strong reliability for CSR (CR=0.986; AVE=0.973) and Profit (CR=0.978; AVE=0.978). The structural model shows CSR has a positive and significant effect on both outcomes: CSR → Lifting (β=0.92; t=59.816; p<0.001; R²=0.847; Q²=0.515) and CSR → Profit (β=0.961; t=80.605; p<0.001; R²=0.924; Q²=0.898). Among indicators, CSR_Overseas (λ=0.988) is the strongest signal within the CSR construct; lifting_bpd (λ=0.935) dominates Y1; and revenue and net profit (both λ=0.989) equally anchor Y2. The findings imply that targeted, context-sensitive overseas CSR can simultaneously stabilize operations and strengthen financial outcomes in international upstream oil and gas.